Does reason for referral to an ultra‐high risk clinic predict transition to psychosis?. Issue 2 (6th June 2018) - Rice, Simon; Polari, Andrea; Thompson, Andrew; Hartmann, Jessica; McGorry, Patrick; Nelson, Barnaby
Abstract : Aim: To examine reasons for referral to a specialist ultra‐high risk (UHR) for psychosis clinic and whether these reasons are associated with risk for subsequent transition to psychosis. Methods: Data for 127 patients referred to the Personal Assessment and Crisis Evaluation clinic were collected by medical record audit. Time to transition to psychosis was calculated from date of referral to time at which the young person was judged by their treating team to be experiencing onset of first episode psychosis. Results: Patients were primarily referred due to attenuated psychotic symptoms and depression (40.2%). There was an association with transition, with those in the attenuated psychotic‐symptom‐only category being more likely to transition. Conclusion: As well as attenuated psychotic symptoms, depression and anxiety were also important reasons for referral indicating that there is a broad clinical phenotype of young people presenting to UHR clinics. Clinical reason for referral may index level of risk for subsequent transition to psychosis.